STRATEGI GURU PAI DALAM MENANAMKAN MODERASI BERAGAMA MELALUI PEMBELAJARAN DIGITAL MULTIKULTURAL DI SEKOLAH DASAR - Bambang Sismedi Saputro; Musa Asy’arie; Sekar Ayu Aryani; Muthoifin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the strategies of Islamic Religious Education (PAI) teachers in instilling the value of religious moderation (wasathiyyah) through multicultural digital learning in elementary schools. The theoretical framework integrates Albert Bandura's Social Learning Theory in the digital ecosystem and the Culturally Responsive Teaching (CRT) approach. The literature review shows a research gap where previous studies discussed religious moderation, digital transformation, and multicultural education partially at the basic education level. The research method used Systematic Literature Review (SLR). Initial identification through the Scopus database netted 55,032 articles, which were filtered using the PRISMA Flowchart to produce 27 reputable final articles (2024-2026) to be analyzed using content analysis. The results show that the integration of digital learning acts as a digital enabler of abstract religious concepts, while the multicultural approach provides an inclusive sociological context for learners. The implications of the research emphasize that the success of instilling tolerance in elementary children depends on the synergy of teachers' Technological Pedagogical Content Knowledge (TPACK) competencies and material sensitivity to diversity. The scientific novelty of this research succeeded in formulating a new instructional model syntax: the Multicultural Digital Values Internalization (MDVI) Model through five operational stages (5D), namely Digital Stimulus, Diverse Dialogue, Digital Modeling, Deep Reflection, and Deeds Doing which is adaptive to the psychological development of elementary school students.